Investigation of Some Physio-Chemical and Microbiological Quality of Fresh Meat Sold Online - Yilmaz, Tahir; Gurdemir, Egemen; Nizamlioglu, Ayse; Akkemik, Yasin; Guner, Ahmet (Selçuk University Press, 2023)
Aim: The research was carried out to draw attention to online fresh meat sales and the precautions to be taken in this area by determining some quality characteristics of fresh meat sold online. Materials and Methods: The pH values of the samples were determined using a digital pH meter and the temperature values were determined using an infrared sensor-operated immersion thermometer. The color values of the samples were determined by measuring the L*, a*, and b* color values with a Chromameter color measuring device. The total viable counts was determined in Plate Count Agar medium, coliform bacteria number in Violet Red Bile Agar medium, Staphylococcus spp. number in Baird Parker Agar medium supplemented with Egg Yolk Tellurite Emulsion using classical culture techniques. Results: The mean pH values of pieced, cubed and minced meat purchased online and customers were respectively 5.62/5.62, 5.64/5.70, and 5.81/5.84. The average temperature values of pieced, cubed, and minced meat purchased online and customers were respectively 11.35/11.1°C, 11.26/11.7°C, and 12.07/12.7°C. Total viable counts of pieced, cubed, and minced meat purchased online and customers were respectively determined as 5.69/5.09, 6.34/5.68, and 7.01/6.36 log10 cfu/g. Temperature values and microbiological results determined in both meat samples purchased online with cold chain and customers without cold chain were similar. Conclusion: In light of the results, it is thought that the temperature values, packaging forms, and shipping conditions of online meat should be more prominent in the reorganization of legislation.
Keywords: cold chain; Veterinary medicine; Denetim; SF600-1100; soğuk zincir; online et; online meat; legislation; 2. Zero hunger